Disclosure and Analysis of Information on Corporate Governance in the Organization’s Sustainability Reporting - A. V. Chepulyanis; A. Yu. Popov (Учёт. Анализ. Аудит, 2025)
The paper’s significance stems from its development of a theoretical and methodological framework for sustainably developing an economic entity, achieved by analyzing and organizing its resources and institutional management tools. The authors used systematic and dialectical approaches, along with observation, generalization, classification, systematization and grouping methods, as the methodological basis for the research. The object of the study was the reporting on the sustainable development of the largest Russian enterprises in various industries. The subject of the research is the accounting and analytical support of activities in organization in the strategy’s implementation of sustainable development in geopolitical instability and globalization of business processes. The novelty of the study is it presents an original economic understanding of “sustainable development”. To successfully implement the organization’s sustainable development strategy, the paper comprehensively classifies and specifies indicators of corporate governance system effectiveness disclosed in integrated reporting. The work systematized the risk factors disclosed in the organization’s ESG reporting for interested users. This paper compares financial and non-financial reporting to highlight signifying sustainability reporting within an organization’s reporting system. The authors have established the assessment standards and key components of the corporate governance and risk management framework.